The wild road home : a novel - Payne, Melissa (Lake Union Publishing, 2024)
"A beautiful and enriching novel about unforgettable love and the power of friends and family by Melissa Payne, the bestselling author of The Night of Many Endings and A Light in the Forest. Mack Anders will do anything for his wife, Daisy. Even die. With the woman he loves fading away from Alzheimer's, Mack fakes his own passing. The insurance makes certain that Daisy will be taken care of with dignity and comfort until the end. In a lonesome cabin in the Wyoming wilderness, he lives off the grid with nothing but thoughts of the past to keep him company and the belief that Daisy is better off without him. Strong-willed eighteen-year-old Brandi has just been released from juvie. Willing to risk everything to save her young brother, Sy, from their unstable mother, Brandi takes him on the run. Her destination is their aunt's house in Casper. Maybe there she can finally find a stable home for Sy. After a busted tire strands them in the remote wildlands of Wyoming, they cross paths with Mack. Brandi quickly realizes this quiet stranger might be their only hope of reaching safety. On an unpredictable road ahead, escape brings these three kindred souls together. But the real world is closing in, and to help Brandi and Sy, Mack will have to come back to life in ways he never imagined." -- ONIX annotation.